2019
DOI: 10.18502/sbrh.v2i2.285
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Positive Psychotherapy on Mental Endurance, Self-Compassion and Resilience of Infertile Women

Abstract: Background: Infertility creates many psychological problems for infertile women. This study aimed to evaluate the effectiveness of positive psychotherapy on mental endurance, self-compassion and resilience of infertile women. Methods: This study was a randomized controlled clinical trial. The statistical population of the present study included infertile women in Tehran in 1396 who visited the infertility centers of Hope and doctor Shariati. In this study among the infertile women who referred to infertility c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Positive psychological interventions enhance coping ability by eliciting positive emotions. Positive emotions can form new meanings to protect individuals from psychological issues and expand psychological well-being and happiness (Mohammadi et al, 2018). The new meaning allows the construction of thinking plans and individual behavior when one is tested with difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Positive psychological interventions enhance coping ability by eliciting positive emotions. Positive emotions can form new meanings to protect individuals from psychological issues and expand psychological well-being and happiness (Mohammadi et al, 2018). The new meaning allows the construction of thinking plans and individual behavior when one is tested with difficulties.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would be valuable to improve psychological wellbeing by focusing more on increasing resilience. [46][47][48] This would allow more room for interventions that help infertile women cope better with their condition and have a better chance at becoming pregnant by lowering their psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…The stigma scale subscale and total mean score of the women in the experimental group after PPT-based training decreased in the posttest compared to the pretest. In their study, Mohammadi et al reported that a 10-session PPT practice was effective on mental endurance, self-compassion, and resistance in Iranian infertile women (Keshavarz-Mohammadi et al, 2018). Ghasemi et al (2017) determined in their study that problem-solving skill training was effective in increasing coping strategies of women receiving intrauterine insemination (IUI) treatment.…”
Section: Discussionmentioning
confidence: 99%